Student Response by Applying A Problem Based Learning Model to Students of SDN Sukapura 01 in The Sub-Theme of My Nation's Cultural Diversity - Adha, Anisa Mutiara; Muharam, Agus (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Student response by applying a problem-based learning model to students of SDN Sukapura 01 in the sub-theme of my nation's cultural diversity. How do students respond by applying a problem-based learning model to students of SDN Sukapura 01 in the sub-theme of my nation's cultural diversity? the method used in problem-based learning. Learning outcomes that are assessed by researchers, from the discussion in chapter IV with the application of the problem-based learning model can improve student learning outcomes in solving problems related to problems that occur in the environment, and by using the problem-based learning model in class IV SD Negeri Sukapura 01 can improve student learning outcomes in the sub-theme of my nation's cultural diversity. The improvement of student learning outcomes can be seen in the results of student processes in each cycle